2013
DOI: 10.1007/s12663-013-0479-6
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Psammomatoid Ossifying Fibroma of Maxillary Sinus: Case Report with Review of Literature

Abstract: Juvenile psammomatoid ossifying fibroma is a rare benign fibro-osseous tumor of the gnathic and extragnathic craniofacial bones, particularly the periorbital, frontal and ethmoid bones. It is slowly progressive with aggressive local growth, invasion and destruction of the surrounding tissue, bone erosion and recurrence after surgical excision. It is distinguished from the other fibroosseous lesions by its age of onset, clinical presentation and aggressive behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 12 publications
0
15
0
3
Order By: Relevance
“…Low-density areas seen on imaging reflect cystic changes. 4,5 In our patient, maxillofacial CT showed that the lesion was hypodense compared with normal bone tissue; it was solid, measuring 37 x 41 x 33 mm, at the level of the first and second premolars inferiorly, extending to the palatine suture medially, filling the left maxillary sinus completely, and eroding the left side of the maxilla.…”
Section: 11mentioning
confidence: 65%
See 2 more Smart Citations
“…Low-density areas seen on imaging reflect cystic changes. 4,5 In our patient, maxillofacial CT showed that the lesion was hypodense compared with normal bone tissue; it was solid, measuring 37 x 41 x 33 mm, at the level of the first and second premolars inferiorly, extending to the palatine suture medially, filling the left maxillary sinus completely, and eroding the left side of the maxilla.…”
Section: 11mentioning
confidence: 65%
“…Recently, El Mofty separated ossifying fibromas into TJOF and PsJOF based on histological criteria. 4,5 PsJOF commonly involves the paranasal sinus and orbital bones, whereas TJOF mainly affects the jawbones, although there is controversy as to whether the maxilla or mandible is affected more often. These lesions are more common in women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Slootweg a unique histological feature of TJOF are thin, garland-like, curvilinear strands of edema, hemorrhage and osteoclasts [17]. JOF clinical and radiographic differential diagnosis should be made from malignancies (osteosarcoma, chondrosarcoma, Ewing's sarcoma, African form of Burkitt's lymphoma, etc); however, the most important radiographic differential diagnoses are COF, FD and mixed odontogenic tumors [15,28]. JOF is usually monostotic and well-demarcated, lacks ground-glass attenuation and contains areas of mineralization while FD tends to be more elongated and ill-defined, demonstrating a slow growth pattern; nonetheless, polyostotic JOF, affecting both the mandible and maxilla, has been reported [29].…”
Section: Discussionmentioning
confidence: 99%
“…JOF is usually monostotic and well-demarcated, lacks ground-glass attenuation and contains areas of mineralization while FD tends to be more elongated and ill-defined, demonstrating a slow growth pattern; nonetheless, polyostotic JOF, affecting both the mandible and maxilla, has been reported [29]. Mixed odontogenic tumors are well demarcated, often intimately associated with unerupted teeth and contain radiodense opacities similar to tooth structures [15,28].…”
Section: Discussionmentioning
confidence: 99%